I Can't Sleep! Death Distress, Self-Control, Bedtime Procrastination, and Substance Misuse - Yilmaz, Fatma Betul; Satici, Seydi Ahmet; Tekin, Emine Gocet (SPRINGER, 2025)
Substance misuse stands as a critical challenge globally, leading to severe repercussions for individuals and society alike, and placing considerable pressure on public healthcare systems and economic stability. This research delves into the predictive relationships between death distress, self-control, bedtime procrastination, and substance misuse. Engaging a diverse cohort of 479 individuals, including those who consume cigarettes and alcohol, aged between 18 and 71 years (Mean = 34.21, SD = 12.61), the study utilized assessments to gauge death distress, self-control, bedtime procrastination, and substance misuse via self-report questionnaires. Through the application of structural equation modeling, the findings revealed that death distress, self-control, and bedtime procrastination are significant predictors of substance misuse behaviors. Furthermore, the analysis highlights that self-control and bedtime procrastination serve as mediating factors in the relationship between death distress and substance misuse. These findings underscore the necessity of identifying and addressing death distress, self-control, and bedtime procrastination to mitigate the effects of substance misuse, thereby emphasizing their significance in prevention and intervention strategies.
Keywords: Substance misuse; Death distress; Self-control; Bedtime procrastination; RELIABILITY; DEPLETION; VALIDITY; Psychiatry